Antifouling property of micro-arc oxidation coating incorporating Cu2O nanoparticles on Ti6Al4V. (3rd October 2017) - Zhao, Dan; Lu, Yuhui; Zeng, Xing; Wang, Zhong; Liu, Shaogang; Wang, Tao
ABSTRACT: To reduce the overgrowth of marine organisms on titanium alloy, this paper presents an antifouling scheme to process ceramic coatings on Ti6Al4V (TC4) using micro-arc oxidation (MAO) combined with nanotechnology. In the study, different concentrations of Cu2 O nanoparticles are added into the electrolytes prepared for MAO process to produce the ceramic coatings. The antifouling performances of the samples are observed by scanning election microscope (SEM), energy dispersive spectrometer and X-ray diffraction. The results demonstrate that nanoparticles of Cu2 O are found in the coating films and the antifouling performance of titanium alloy after MAO treatment is obviously enhanced, in which antibacterial rate is up to 95.25%. The Ti-MAO-10.0g/LCu2 O group has the highest antibacterial rate of 99.74%.